CONGDARDIR: AN INNOVATIVE TRADITIONAL GAME-BASED MEDIUM TO ENHANCE HIGH SCHOOL STUDENTS SELF-AWARENESS - Ananda, Seha; Setyaputri, Nora Yuniar; Puspitarini, Ikke Yuliani Dhian (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
This study aims to develop and examine the feasibility of a traditional game-based medium, derived from the game "congklak," named CONGDARDIR (Congklak Kesadaran Diri Congklak), as a tool in group counseling services to enhance high school students’ self-awareness. The research employed a R&D method using the ADDIE model, consisting of five stages: analyze, design, develop, implement, evaluate. The medium was validated by subject matter experts, media experts, and users (school counselors), with feasibility percentages of 94%, 86%, and 93% respectively, categorizing it as "highly feasible." The final product consists of a congklak board, game seeds, and reflection cards designed based on self-awareness indicators. The trial was conducted with eight 11th-grade students selected through purposive sampling due to their low level of self-awareness. Scores averaged 88.13 (pretest) and increased to 136.13 (posttest). The Shapiro-Wilk normality test indicated normally distributed data. The homogeneity test yielded a significance value of 0.832 (p > 0.05), indicating homogeneous variance between pretest and posttest scores. The paired sample t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant improvement following the intervention. Therefore, the CONGDARDIR medium has proven statistically and practically effective as a group counseling tool to enhance students’ self-awareness through a fun, reflective, and culturally grounded approach. Counselors are encouraged to continuously utilize this medium in guidance services. Schools are also expected to support its use as part of student character development programs. Future researchers are recommended to further develop this medium and test its implementation in broader school contexts.